Wetting mechanism and bending property of Cu/Al2O3 laminated composites with pretreated CuO interlayer. Issue 11 (1st August 2020) - Li, Fuping; Wang, Wenxiang; Dang, Wei; Zhao, Kang; Tang, Yufei
Abstract: Addition of oxygen in the interface between Cu and Al2 O3 can significantly improve the wettability. In the present work, Cu/Al2 O3 laminated composites were fabricated by bonding Cu foils with CuO-coated Al2 O3 plates. Before bonding, the coated Al2 O3 plates were pretreated at different temperature in the air. The effect of pretreated temperature on the interfacial microstructure, wettability and bending property were investigated. Phase composition in the interface after wetting test was characterized according to the thermodynamics of Cu–O system. The wetting mechanism and bending failure mode of Cu/Al2 O3 laminated composites were also analyzed. Pretreated temperature significantly influences the wettability and bending strength of the composites. The contact angle decreased to about 22° when the pretreated temperature equal to 1100 °C. Continuous CuAlO2 in the interlayer is beneficial to the wettability between Cu melt and Al2 O3, while other phases such as Cu2 O and CuAl2 O4 would increase the contact angle. Crack formation and propagation are the main failure mode of Cu/Al2 O3 laminated composites during bending test. Different from the wettability, Cu/Al2 O3 laminated composites fabricated with pretreated temperature at 1050 °C show the highest bending strength, although the contact angle is not the lowest on this condition. The reason is illustrated through analyzing the bending failure mode.